Study of vitamin D level in patients with different etiologies of chronic liver disease and its correlation with Child Pugh class in a tertiary care centre in North India - Verma, Ajit Kumar; Gautam, Shri Krishna; Giri, Richa; Singh, Reena; Gupta , Vishal (International Journal of Research in Medical Sciences, 2023)
Background: Skeletal manifestation in liver diseases represents the minimally scrutinized part of the disease spectrum. Vitamin D has a central role in developing hepatic deficiency of osteodystrophy in patients with chronic liver disease. This study aimed to investigate vitamin D levels and their and their relationship with disease advancement in these patients according to child Pugh-score. Aims and Objectives were study of vitamin D level in patients with different aetiology of chronic liver disease and its correlation with child Pugh score. Methods: This was a cross sectional study conducted over 200 patients after applying inclusion and exclusion criteria in patients with different etiology of chronic liver disease. Results: In our study total (N=200), 152 patients of alcoholic liver disease 41 patients having deficient vitamin D, 79 having insufficient vitamin D level and 32 patients having normal vitamin D level. Patients of chronic liver disease also have negative correlation on vitamin D level with Child Pugh score. In our study it was found that patients having higher Child Pugh score there is more chance of having vitamin D deficiency and insufficiency than the patient’s low Child Pugh score. Conclusions: The prevalence of vitamin d deficiency in patients with CLD was found to be having a significant correlation with increasing CTP score with p value <0.001.